EFL students' perceptions of Talking Stick in English speaking class - Nisa, Rahmatun; Helmanda, Cut Mawar; Manita, Arfares (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2022)
The study aimed to investigate the English as a foreign language (EFL) students opinions on the use of Talking Stick in helping to improve their English speaking ability at a high school in Aceh Province, Indonesia. The study employed a quantitative method. The sample of the study was 15 first year students of a public senior high school in Banda Aceh, Aceh, Indonesia. The study selected the sample by using the purposive sampling, as the students have had Talking Stick technique in their English speaking class. To collect the data, the study disseminated questionnaires to the students. The results showed that the students had positive responses towards the use of Talking Stick in learning English speaking. The study recommends that such a technique can be applied more in other English classes in Indonesia.